Improvement of technical skills of 14-16 years old athletes who are engaged in aesthetic group gymnastics - Dolbysheva, N.; Kidon, V.; Kovalenko, N.; Holoviichuk, I.; Koshcheyev, A.; Chuhlovina, V. (Journal of Physical Education and Sport, 2020)
The purpose was to introduce in the training process the author's technique for improving technical skills at the stage of specialized basic training of the third year of training and to determine its effectiveness for the technical readiness indicators and the result of competitions. The object of the study was the technical preparedness of gymnasts. Participants - 2 teams of athletes of Ukraine with aesthetic group gymnastics (Viva Victoria team of Dnipropetrovsk region and Vivend team of Zaporizhzhya region). Each team consisted of 12 gymnasts aged 14-16 years, which meets the requirements of international rules on aesthetic group gymnastics. Results. Introduced author's technique for improving technical skills in the training process contributed to the improvement of technical training of gymnasts in the data of such tests as "series including any three different body movements" and "supplementary difficultly" at p = 0.001, and an increase of 11.74%. Quantitative and qualitative correlation relationships between technical readiness indicators increased (up to 10 interconnections out of 10 possible) at a reliability of p = 0.05-0.01. The result of the team's competitive activity, both at the national and at the world levels, increased by an average of 0.45 points (9.47%) and execution - by 0.40 points (5.13%). Conclusions. Planning in the training process of the author's technique for improving the technical skill of female athletes engaged in aesthetic group gymnastics, contributed to the improvement of technical readiness and the result of competitive activity, which gives the basis for its practical implementation in the system of training of female gymnasts at the stage of specialized basic training.